2019
DOI: 10.1111/jgh.14617
|View full text |Cite
|
Sign up to set email alerts
|

The balance of type 1 and type 2 immune responses in the contexts of hepatitis B infection and hepatitis D infection

Abstract: Background and Aim Hepatitis delta virus (HDV) infection is the most rapidly progressive chronic viral hepatitis. Little is understood about the immune responses to HDV. This study aims to characterize the systemic immune environments of hepatitis B virus (HBV) and HDV patients at various disease stages. Methods A total of 129 subjects were evaluated: 53 HBV, 43 HDV, and 33 healthy controls. HBV and HDV subjects were categorized by aspartate aminotransferase to platelet ratio index (APRI) into mild (APRI < 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
3
15
0
Order By: Relevance
“…Interestingly, TNF-a levels are higher in HDV patients and there is a close correlation between TNF-a and the severity of the disease. 36 Thus, taken together, these data indicate that TNF-a is involved in HDV-induced liver damage and suggest that anti-TNF-a might be a possible treatment aimed at attenuating liver damage in patients with chronic HDV infection and/or that it might be useful in cases of fulminant hepatitis associated with HDV infection. Studies to determine the source of TNF-a are ongoing.…”
Section: Discussionmentioning
confidence: 73%
“…Interestingly, TNF-a levels are higher in HDV patients and there is a close correlation between TNF-a and the severity of the disease. 36 Thus, taken together, these data indicate that TNF-a is involved in HDV-induced liver damage and suggest that anti-TNF-a might be a possible treatment aimed at attenuating liver damage in patients with chronic HDV infection and/or that it might be useful in cases of fulminant hepatitis associated with HDV infection. Studies to determine the source of TNF-a are ongoing.…”
Section: Discussionmentioning
confidence: 73%
“…However, to the best of our knowledge, there are no data on the cytokine profile during the acute phase of HDV superinfection in humans, and the data are also very limited for the chronic phase. In a recent study performed at a single time point in patients with chronic hepatitis D, the levels of IFN-␥ and IL-12 p70 did not differ compared to those of controls, whereas IL-17A, IL-10, CXCL9, and TNF-␣ were found to be increased (42). Moreover, it has been shown that circulating CD4 ϩ and CD8 ϩ T cells from patients with chronic hepatitis D express low levels of IFN-␥ and TNF-␣ upon in vitro activation (43).…”
Section: Discussionmentioning
confidence: 80%
“…Cytokine secretion varies among subsets of Th2 and Treg cells. Notably, a Th2 bias in the Th1/Th2 cytokine balance is not conducive to a successful antiviral immune response [73,[170][171][172][173][174].…”
Section: Immune Checkpoints Affect Chronic Hepatitis Virus Infection mentioning
confidence: 99%